2021
DOI: 10.1039/d0cy02277b
|View full text |Cite
|
Sign up to set email alerts
|

Syngas to light olefin synthesis over La doped ZnxAlyOz composite and SAPO-34 hybrid catalysts

Abstract: The direct transformation of syngas to light olefins is a highly attractive route for the synthesis of light olefins. The La doped ZnxAlyOz catalyst was prepared with various precipitating agents,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…When Zn x Al y O z oxides were created using different precipitating agents, Raveendra et al discovered that the oxides prepared with NH 3 ÁH 2 O as the precipitating agent had stronger catalytic effects. 20 This finding implies that different oxides are appropriate for different acid-base characteristics. In the same way, Yang et al found that the GaMnOx oxides they made using NH 3 ÁH 2 O worked better as a catalyst when mixed with SAPO-34.…”
Section: Introductionmentioning
confidence: 99%
“…When Zn x Al y O z oxides were created using different precipitating agents, Raveendra et al discovered that the oxides prepared with NH 3 ÁH 2 O as the precipitating agent had stronger catalytic effects. 20 This finding implies that different oxides are appropriate for different acid-base characteristics. In the same way, Yang et al found that the GaMnOx oxides they made using NH 3 ÁH 2 O worked better as a catalyst when mixed with SAPO-34.…”
Section: Introductionmentioning
confidence: 99%
“…In the petrochemical industry, methanol and lower olefins such as ethylene, propylene, and butylene, and aromatics like benzene, toluene, and xylene are produced as main chemicals and then further converted into industrial products. [2][3][4][5][6][7] The world's utilization of fossil fuels and chemicals which are derived from non-replaceable petroleum resources has increased remarkably. The depletion of fossil fuels and hydrocarbons increases environmental pollution and the emission of CO 2 into the atmosphere, which leads to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Fischer–Tropsch synthesis (FTS) is a traditional strategy to convert syngas into hydrocarbons over Fe and Co catalysts; however, the Anderson–Schulz–Flory (ASF) model in FTS limits the selectivity of C 2–4 hydrocarbons (including olefins and paraffins), which is no more than 58%. , Recently, an elegant oxide–zeolite (OX-ZEO) route was proposed to selectively convert syngas into olefins (STO), liquid fuels and aromatics depending on the topologies of the zeolites, , which breaks the ASF distribution in FTS. A number of metal oxides, such as ZnCrO x , , Zn–ZrO 2 , , ZnAlO x ,, and MnGaO x , and several kinds of zeolites, including SAPO-34, SAPO-18, , AlPO-18, and SSZ-13, , have been intensively studied. In such an OX-ZEO catalyst system, the metal oxide is responsible for the syngas activation to generate intermediates like methanol and ketene, while the zeolite plays the role in tandem conversion of intermediates to target products .…”
Section: Introductionmentioning
confidence: 99%